The Rise оf Powers: the United States Or «City On A Hill» (Journal of history, 2019)
There have been efforts to define the role of the United States in Internited States in Inter in International Relations as an American discipline in an international environment where the USA arose as the sole superpower. In this context, it can be said the Realist/Neorealist school, which is one of the established theoretical schools in international relations, is undergoing a change. In fact, some representatives of the Realist school, who are head over heels due to the USA’s «privileged» and «superior position», have been criticised for acting in accordance with views that are close to «hegemony» and «neoliberal views» and ceasing to be Realists. The central role of states by which an ordinary state becomes a «great power», which is one of the most frequently criticised concepts of the Realist approach, the developments that lead to this process and the factors such as the economic and military potentials of great powers are among the subtopics that will be covered extensively in this study. The state to be able to defend its national interests, it needs to be powerful. In this context, the purpose of this paper is listing of the important historical events to shed light on the status of the US as «great power» by citing the events that contributed to his rise.